New Approaches to Nonstate Armed Actors - Williams, Kenneth H. (Marine Corps University Press (MCUP), 2012)
The chapters incorporate presentations from a panel at the Middle East Institute's 64th Annual Conference, held on November 4, 2010, in Washington, DC. Although the focus of the conference itself was on the Middle East, this panel discussion ranged beyond the region and reflected research on nonstate armed groups from around the world.